C3 molecular structural and histopathological analyses in a pediatric case of atypical hemolytic uremic syndrome with life-threatening gastrointestinal bleeding—a case report - Enya, Takuji; Miyazaki, Kohei; Kuge, Sakina; Morimoto, Yuichi; Kondou, Hiroki; Sakata, Naoki; Joh, Kensuke; Nagano, China; Nozu, Kandai; Ito, Nobutoshi; Hakata, Yoshiyuki; Sugimoto, Keisuke; et al. (Frontiers in Pediatrics, 2026)
Atypical hemolytic uremic syndrome (aHUS) is a rare, life-threatening disease characterized by uncontrolled complement activation and is associated with various genetic factors, including multiple variants at the gene locus encoding the complement component 3 (C3). However, only a few functional amino acid substitutions have been identified in C3. We report a pediatric case of aHUS presenting with refractory hypertension and massive gastrointestinal bleeding. Comprehensive histopathological, immunohistochemical, genetic, and molecular structural analyses were performed. Biopsy specimens were stained for renin and the membrane-attack complex of the complement system (C5b-9). Plasma levels of the Ba fragment of complement factor B were measured to evaluate the alternative pathway activation. Genomic DNA was obtained with consent and analyzed by targeted next-generation sequencing using a custom gene panel, followed by Sanger sequencing for variant confirmation. The possible effects of the identified amino acid substitution on the molecular structure of C3 were analyzed using computer-aided simulation with MODELLER and DoGSiteScorer. As a result, the juxtaglomerular apparatus was hyperplastic and intensely stained for renin. Endothelial cells of renal and intestinal blood vessels were positive for C5b-9. The plasma Ba level was elevated compared to the control level. The ileal and colonic mucosae were denuded and highly edematous, with epithelial cells undergoing regenerative and metaplastic changes in the active phase. Mucosal blood vessels contained intraluminal red cell fragments and neutrophils attached to swollen endothelial cells. However, the colonic mucosa showed near-normal histology after disease convalescence. Genetic analyses identified a single nucleotide C3 variant NM_000064.4(C3):c.4811T>C (p.Met1604Thr), resulting in an M1604T substitution in the functional C345C domain. Molecular structural analyses indicated that this amino acid substitution can cause the formation of a large cavity within the hydrophobic core of the C-terminal domain, possibly destabilizing the spherical structure of C3. Our study highlights that the M1604T substitution in the C3 C345C domain may drive the observed excessive complement activation, C5b-9 deposition on endothelial cells, and severe circulatory disturbances in the intestinal mucosa.